Leveraging Information and Communication Technology (ICT) to Enhance EFL Students' 4C Skills - Fima, Muhamad Fazleyevin; Melvina, Melvina; Yulmiati, Yulmiati (English Teaching and Linguistics Journal (ETLiJ), 2024)
This study seeks to explore the 21st-century skills that English as a Foreign Language (EFL) students develop through the use of Information and Communication Technology (ICT) in the classroom. Specifically, it aims to examine how students at SMA N 3 Padang, a high school in West Sumatra, Indonesia, acquire the 4C skills—communication, collaboration, creativity, and critical thinking—when using ICT. The research follows a quantitative approach, utilizing a survey method. A random sampling technique was applied, selecting 115 students from a total population of 385. Data were collected through a questionnaire designed to assess 21st-century skills for EFL students, administered via Google Forms. Descriptive statistics were used to analyze the results and determine the percentage of students demonstrating these skills. The findings revealed that students exhibited notable proficiency in all four 21st-century skills, with communication at 73.6%, collaboration at 74%, creativity at 74.4%, and critical thinking at 75.4%. These results highlight the positive role of ICT in fostering students' 4C skills, with the data reflecting moderate to high levels of achievement. In conclusion, the study demonstrates that students effectively develop these crucial competencies through ICT integration in their educational experience.